Neoliberalismo e políticas educacionais : estudo do Pacto pela Educação em Goiás (2011-2018) - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
This work is the result of research developed in the Interdisciplinary Graduate Program in Education, Language and Technologies, of the Campus of Socioeconomic and Human Sciences, of the State University of Goiás (PPG-IELT / UEG), Campus Anápolis. We sought to understand how the Pact for Education Goiás program launched in 2011, contributes to the construction and maintenance of bourgeois society. The main objective was to analyze how the Pact for Education in Goiás consolidates a model of bourgeois society and how, in its core, there are liberal political proposals that advocate the values inherent in third way capitalism. The research was developed with the perspective of historical materialism as a method, with documentary and bibliographic sources, such as the base document of the Pact for Education in Goiás, the National Education Plan, State Education Plan, Law of Education Guidelines and Bases 9,394 / 96 and decrees and complementary laws that direct education in the State of Goiás. We also resort to recent research that seeks to understand other relations of the Pact for Education in Goiás through its prerogatives and impositions that directly result in school routine and teaching practice. In this sense, the educational policy of Goiás was contextualized in a national scenario, which in turn is also part of a larger and more complex set of policies aimed at education developed by multilateral organizations at the service of capital and hegemonic nations in the capitalist world. . The actions of the State, for the effectiveness of the Pact for Education, are in line with the neoliberal logic and the needs of the market that demand a school adequate to the new patterns of economic accumulation. It is clear that teachers, as intellectuals, are fundamental to sustain educational reform as producers and reproducers of a neoliberal ideology based on competition, individualism and meritocracy. The private devices of hegemony of the dominant classes also contribute effectively and efficiently to the creation of a positive educational aura with the educational reform in Goiás. In concrete life, it can be seen that, in this alienating education model and focused on the interests and dictates of the market, the precariousness of the teaching profession as well as the construction of its total privatization are results that are being built daily
Neoliberalism and educational policies: study of the Pact for Education in Goiás (2011-2018)
Keywords: Pacto pela Educação em Goiás - Neoliberalismo; Políticas Públicas Educacionais - Neoliberalismo; Políticas Públicas Educacionais - Hegemonia; Neoliberalism - Pact for Education in Goiás; Neoliberalism - Public Educational Policies; Public Educational Policies - Hegemony; CIENCIAS HUMANAS::EDUCACAO; PLANEJAMENTO E AVALIACAO EDUCACIONAL::POLITICA EDUCACIONAL